THE INFLUENCE OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON INTENTION TO USE GOJEK APPLICATION AND ITS IMPACT ON PURCHASE DECISION OF GOJEK SERVICES - Hutagalung, Ulianto; Sukriah, Yani; Ritonga, Nursakinah (The International Journal of Accounting and Business Society, 2021)
Purpose — The purpose of this reseacrh is to explain and analyze the influence of Perceived Usefulness  and Perceived Ease of Use on Intention to Use the Gojek application and its impact on Gojek service purchasing decisions.Design/methodology/approach — This study uses a quantitative approach using explanatory research. The population of this study is The citizen of Padangsidimpuan City, North Sumatera who use Gojek Services at least five times a month. To determine the sample of the population, researchers used Machin & Champbell (1987)  formula to obtain the number of respondents as many as 115 people. The sampling technique of this study is the nonprobability sampling technique. The method of data collection used a questionnaire distributed to the respondent and calculated using a Likert scale. Data analysis methods consist of test instruments, research requirements testing, and hypothesis testing with path analysis by SPSS.Findings — The results of this study indicate that the Perceived Usefulness and Perceived Ease of Use has a positive and significant effect on the Intention to use Gojek application. Practical Implications — Perceived Usefulness and Intention to Use Gojek application has a positive and significant influence on purchasing decisions, while the Perceived Ease of Use has no significant influence on Purchasing Decisions.Keywords Perceived Usefulness, Perceived Ease of Use,  Intention to Use, Purchase Decision, GojekPaper Type Research Paper.